Regulatory effects of vitamin E nano-emulsion on blood metabolites, immunological variables, testicular architecture, and sperm ultrastructure of heat-stressed V-line rabbit bucks - Ali Ali El-Raghi; Walaa M. Essawi; Sameh A. Abdelnour; Ibrahim Talat El-Ratel; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Mahmoud A. E. Hassan; Maged A. A. Abd El-Hady; Maged A. Aboul-omran; Ahmed N. F. Neamat-Allah; Shimaa A. Amer; Simon J. Davies; et al. (Italian Journal of Animal Science)
The study investigated the beneficial effects of vitamin E-loaded nano-emulsion (NEVE) on hemato-biochemical changes, oxidative stress, inflammatory responses, immunological variables, and semen quality in heat-stressed rabbit bucks. Forty adult V-line rabbit bucks were randomly assigned to four groups and fed diets containing NEVE at 0 (NEVE0), 50 (NEVE50), 100 (NEVE100), and 200 (NEVE200) mg/kg for 12 weeks. The NEVE had a mean particle diameter of 32.6 nm, a polydispersity index of 0.6, and a zeta potential of −31.1 mV. The dietary NEVE significantly improved the hematological, blood protein, lipid profile, and liver functions of rabbit bucks (p < 0.05). The NEVE200 treated group showed higher levels of nitric oxide, TAC, and SOD in blood serum and seminal plasma compared to the control group (p < 0.05). Meanwhile, levels of MDA, IL-4, and TNF-α were significantly shrunken in response to the dietary treatment (p < 0.0001), while the IgA and IgG were improved in the NEVE100 and NEVE200 groups. The NEVE200 exhibited higher progressive motility, ejaculate volume, viability, and better libido (lower reaction time) than the untreated group (p < 0.05). TEM images illustrated that NEVE200 exhibited higher sperm cells with a normal structure, intact plasma membranes, and acrosomes than the other groups. Moreover, testicular architecture was improved with NEVE supplementation. Overall, the dietary addition of NEVE at 100 or 200 mg/kg could be an effective strategy to improve the health and semen quality of rabbit bucks during hot climates.